Method for Calculating Parameters of Mechanical Properties of Rocks for Simulation of Hydraulic Fracturing - A-G. G. Kerimov; E. G. Kerimova; S. B. Beketov; T. A. Gunkina; V. G. Kopchenkov (Наука. Инновации. Технологии)
Introduction. The inability to accurately predict the hydraulic fracturing gradient (fracking) occasionally leads to catastrophic consequences, for example, to the disclosure of natural cracks in the object, which was not planned. It results in very expensive problems during the construction of the well. The hydraulic fracturing gradient is an extremely important parameter that needs to be taken into account when designing the well wiring.Materials and research methods. To simulate hydraulic fracturing, laboratory complexes are often used, where experimental studies of rock samples taken in the well are carried out. The article presents a scheme for determining the propagation velocity of longitudinal and transverse waves in laboratory conditions in order to calculate the Poisson’s ratio.Research results and their discussion. The system works by exciting an ultrasonic acoustic wave at the end of a cylindrical core sample, followed by recording the arrival times of waves at the end of the core end. Knowing the length of the core sample, the velocities of the longitudinal and transverse waves are calculated. The velocity is equal to the ratio of the length of the sample to the time of arrival of the wave at the opposite end of the sample. However, often core samples taken from the well in which it is planned to perform hydraulic fracturing are not always representative, often in practice there is a low percentage of core sampling. The article presents a method for calculating some initial parameters for modeling hydraulic fracturing, based on field and geophysical data. The calculation includes the application of a comprehensive analysis of the data of geophysical studies of wells by broadband acoustic logging and the results of numerical calculations of the physical and mechanical properties of rocks.Conclusions. The information obtained allows one to quickly and efficiently perform the necessary calculation of the strength properties of the walls of the well, perform hydraulic fracturing efficiently, determine the characteristics of the elastic medium practically on a real-time scale, as well as design other technological processes using the fundamental laws of underground hydrodynamics and analysis of the results of geological and field studies. It should be noted that in the absence of logging material by the broadband acoustic logging method, it is proposed to use the data of standard acoustic logging, the implementation of which is regulated in all wells during their construction, and through it to calculate the speed of the transverse wave run based on tabular values of the velocities of longitudinal and transverse waves in rocks.